(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2024)
Multiple researchers and the three-body problem highlight a potential instability in the Classic model of the Solar System, indicating a possible fundamental instability in the system’s dynamics. Therefore, we consider that the Classical model does not reflect reality, and we propose an alternative model that we call: Theory of Dynamic Interactions, providing a brief exposition of the studies carried out by Advanced Dynamics, until defining a Rotational Dynamics of Interactions, applicable to bodies subjected to multiple pairs of successive non-coaxial forces.